Immunophenotypic classification of canine malignant lymphoma in formalin-fixed, paraffin wax-embedded specimens using CD3 and CD79a cell markers - Nesbit, J.W. (University of Pretoria, 2013)
Dissertation (MMed Vet (Pathology))--University of Pretoria, 1999.